The importance of nutrition in the modulation of metabolic oxidative stress in cadets - Vieira, Douglas Sousa Brasilino; Silva, Herlan Sousa da; Santos, Jayane Santana; Nolêto, Lariza dos Santos; Santos, Sarah Letícia Lima; Carvalho, Camila Maria Vieira de; Silva, Maria Keiliane Fernandes de Souza da; Barros, Italo Silva; Morais, Kayky Oliveira; Nolêto, Vanessa Lima; Nascimento, Marcos Antonio do; Nolêto, Diandra Carvalho de Sá (Seven Editora, 2024)
The objective of this article is to discuss the importance of food in the modulation of metabolic oxidative stress in cadets. Stress is a natural response of the body when we are faced with a dangerous situation, thus causing physical and psychological changes. Cadets experience high levels of stress due to the physical and mental demands of military life. Both chronic stress and intense training lead to a greater generation of reactive oxygen species (ROS), requiring the action of antioxidant agents to neutralize ROS, avoiding metabolic oxidative stress (EOM). The stress level and strenuous training of cadets can lead to an imbalance of the redox system, due to the accumulation of reactive oxygen species and the depletion of antioxidants, causing oxidative stress. Diet can act by modulating EOM through nutrients such as vitamins C, E and A, zinc, selenium, flavonoids and carotenoids. DOI:https://doi.org/10.56238/sevened2024.012-023